KOMITMEN PEMBERANTASAN KORUPSI DI SEKTOR KESEHATAN PEMERINTAH - , FAISAL ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Background: Corruption has become a fundamental problem even rooted so that it was difficult to eradicate. Prevention of corruption have also implemented in Indonesia, however, corruption is still going on in various sectors. The public health sector is one area that is very prone to corruption. Corruption cases that have occurred in the public health sector to be a question about government's commitment to combating corruption. This study also provides information about the opportunities and prevalence of public health sector corruption. Method: This research is quantitative descriptive with cross sectional study types. The unit of analysis is the government health institutions. Respondents are IKM UGM students and alumnis who work in the public health sector and they were assumed to know the real condition of the workplace and will be the leaders in the future. The survey was conducted from April 27th until June 17th,2013 Result: Respondents who participated in this study are 152 respondent. 80% individual desires against corruption, but abandonment rate in corruption 63%, leaders commitment 36%. Corruption situation occurs in a lack of transparency and accountability is 69%. Most form of corruptions are lightly corruption (absenteeism) 62%, and severe corruption (gratuities) 44%. Conclusion: Commitment to fighting corruption in the public health sector is still low and limited to individual commitments. Corruption occurs in almost all instances. Highest prevalence of corruption is lightly corruption. While the chances of corruption occurs due to lack of transparency.